2023
DOI: 10.1177/08897077231186228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking Marijuana on the Respiratory System: A Systematic Review

Jorge Vásconez-González,
Karen Delgado-Moreira,
Belén López-Molina
et al.

Abstract: Background: The prevalence of marijuana use and its derivatives has surged over the past century, largely due to increasing legalization globally. Despite arguments advocating its benefits, marijuana smoking exposes the lungs to harmful combustion byproducts, leading to various respiratory issues such as asthma, pneumonia, emphysema, and chronic obstructive pulmonary disease. Methods: We embarked on an extensive literature search, utilizing PubMed/Medline, Scopus, Web of Science, and Google Scholar databases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
2
0
1
Order By: Relevance
“…This aspect of our study offers a new perspective in light of the broader discourse on cannabis and respiratory health, including its potential therapeutic applications [15,16]. However, the intricacies of cannabis's impact on respiratory and overall health are not fully understood, and our findings highlight the need for further research in this area [17,18]. The younger age profile of cannabis users, as identified in our study, might contribute to this observed difference, given the general trend of better clinical outcomes in younger patients.…”
Section: Discussionmentioning
confidence: 77%
“…This aspect of our study offers a new perspective in light of the broader discourse on cannabis and respiratory health, including its potential therapeutic applications [15,16]. However, the intricacies of cannabis's impact on respiratory and overall health are not fully understood, and our findings highlight the need for further research in this area [17,18]. The younger age profile of cannabis users, as identified in our study, might contribute to this observed difference, given the general trend of better clinical outcomes in younger patients.…”
Section: Discussionmentioning
confidence: 77%
“…Other thoracic complications, such as lung cancer, myocardial infarction, and alveolar hemorrhage, are less common. 1 - 3 …”
mentioning
confidence: 99%
“…Outras complicações torácicas, como câncer de pulmão, infarto do miocárdio e hemorragia alveolar, são menos comuns. (1)(2)(3)…”
unclassified